Восприятие экономических изменений и стратегии выживания домохозяйств - Горбачик, А. (Социология: теория, методы, маркетинг, 2001)
The author analyzes the peculiarity of perception of economic changes for the last eight years by different groups of the population and the forms of household adapting to fast economic changes in Ukraine. The regional features of economic situation evaluation and factors influencing on these evaluations are considered. Several strategies of household adapting (survival) are discussed from the point of their correspondence to general market reforms in the country. The article is based on data of monitoring public opinion survey and qualitative research of social changes in the households.